2021
DOI: 10.1038/s41598-021-91155-w
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding putative bicarbonate transporters as a missing molecular link between molt and mineralization in crustaceans

Abstract: During their life, crustaceans undergo several molts, which if theoretically compared to the human body would be equivalent to replacing all bones at a single event. Such a dramatic repetitive event is coupled to unique molecular mechanisms of mineralization so far mostly unknown. Unlike human bone mineralized with calcium phosphate, the crustacean exoskeleton is mineralized mainly by calcium carbonate. Crustacean growth thus necessitates well-timed mobilization of bicarbonate to specific extracellular sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Calhoun & Zou (2016) proposed the existence of hypothetical bicarbonate transporters in both apical and basolateral membranes of epidermal cells in their mineralization model that explains the formation of carbonate salts in the hardening exoskeleton. Abehsera et al (2021) recently reported genes encoding putative bicarbonate transporters in the epidermis of the crayfish, Cherax quadricarinatus , with CqSLC4A1 presumably located in the apical membrane and CqSLC4A7 putatively residing in the basolateral membrane. Whether increased postecdysial mineralization in the exoskeleton following CO 2 treatment occurs concurrently with an elevated bicarbonate influx urgently needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Calhoun & Zou (2016) proposed the existence of hypothetical bicarbonate transporters in both apical and basolateral membranes of epidermal cells in their mineralization model that explains the formation of carbonate salts in the hardening exoskeleton. Abehsera et al (2021) recently reported genes encoding putative bicarbonate transporters in the epidermis of the crayfish, Cherax quadricarinatus , with CqSLC4A1 presumably located in the apical membrane and CqSLC4A7 putatively residing in the basolateral membrane. Whether increased postecdysial mineralization in the exoskeleton following CO 2 treatment occurs concurrently with an elevated bicarbonate influx urgently needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In crustaceans, molting is a process for shedding the old exoskeleton that limits the growth of organisms ( Gao et al, 2015 ; Luo et al, 2015 ). The shrimp body may mineralized during the inter-molt stages ( Abehsera et al, 2021 ). After every ecdysis, the shrimp has shed the old shell and the new exoskeleton is still soft and flexible, and it needs to expand the new exoskeleton to make room for the growth of new tissues by absorbing water ( Chang, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecdysis initiates the release of calcium biphosphate from gastroliths (Abehsera et al, 2018a). In the freshwater C. quadricarinatus, transportation of calcium salts to and from the gastrolith depends on two bicarbonate transporters from the SLC4 family distributed in the cuticular epithelium and in the gastrolith discs with different activation times (Abehsera et al, 2021). In this crayfish and in the prawn Penaeus japonicus, the deposition of calcium salts within the cuticle is probably mediated through CPs with chitin-binding and calcium-binding abilities such as the calcification-associated proteins (Ikeya et al, 2001;Roer et al, 2015).…”
Section: ) Neuropeptides Regulate Stereotypical Ecdysis Behavioursmentioning
confidence: 99%